2015
DOI: 10.1007/s10549-015-3527-8
|View full text |Cite
|
Sign up to set email alerts
|

Deleterious BRCA1/2 mutations in an urban population of Black women

Abstract: Information on the prevalence of deleterious BRCA1 and BRCA2 (BRCA1/2) mutations in clinic-based populations of Black women is limited. In order to address this gap, we performed a retrospective study to determine the prevalence of deleterious BRCA1/2 mutations, predictors of having a mutation, and acceptance of risk-reducing surgeries in Black women. In an urban unselected clinic-based population, we evaluated 211 self-identified Black women who underwent genetic counseling for hereditary breast–ovarian cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 32 publications
2
10
0
2
Order By: Relevance
“…It is certainly possible that mutations labeled as a variant of unknown significance may prove important in the future, although the majority are reclassified as benign polymorphisms. 5961 We also recognize our results are influenced by the overrepresentation of certain cancer lineages, including ovarian (n = 9,630), NSCLC (n = 8,119), CRC (n = 6,650), breast (n = 5,910), and endometrial (n = 5,540) cancers in the Caris database. And finally, although additional genes were of interest to evaluate (including EMSY and RAD51C ), they either were not included in the Caris targeted NGS600 platform or variants have not been interpreted by a Caris geneticist and, as such, were excluded from this analysis.…”
Section: Discussionmentioning
confidence: 70%
“…It is certainly possible that mutations labeled as a variant of unknown significance may prove important in the future, although the majority are reclassified as benign polymorphisms. 5961 We also recognize our results are influenced by the overrepresentation of certain cancer lineages, including ovarian (n = 9,630), NSCLC (n = 8,119), CRC (n = 6,650), breast (n = 5,910), and endometrial (n = 5,540) cancers in the Caris database. And finally, although additional genes were of interest to evaluate (including EMSY and RAD51C ), they either were not included in the Caris targeted NGS600 platform or variants have not been interpreted by a Caris geneticist and, as such, were excluded from this analysis.…”
Section: Discussionmentioning
confidence: 70%
“…Note that only 11 published studies were found that included male BRCA1/2 PSV carriers, but no additional BRCA1/2 PSVs were identified from these reports. Forty‐eight studies were included in the present report: 16 studies of Sub‐Saharan Africans (Awadelkarim et al, ; Biunno et al, ; Diez et al, ; Elimam et al, ; Fackenthal et al, ; Fackenthal et al, ; Francies et al, ; Gao et al, ; Luyeye Mvila et al, ; Stoppa‐Lyonnet et al, ; van der Merwe et al, ; Zhang et al, ; Zhang et al, ; Zhang, Fackenthal, Huo, Zheng, & Olopade, ; Zheng et al, ; Zoure et al, ), 27 of African Americas (Arena et al, ; Arena et al, ; Arena et al, ; Castilla et al, ; Churpek et al, ; Dangel et al, ; Futreal et al, ; Ganguly, Dhulipala, Godmilow, & Ganguly, ; Q. Gao, Neuhausen, Cummings, Luce, & Olopade, ; Q. Gao, Sveen, Cummings, & Olopde, ; Q. Gao et al, ; Gayol et al, ; Haffty et al, ; Hall et al, ; John et al, ; Kanaan et al, ; Kedar‐Barnes et al, ; Lynce et al, ; Martin et al, ; Miki et al, ; Nanda et al, ; Olopade et al, ; Pal et al, ; Pal et al, ; Pal, Permuth‐Wey, Holtje, & Sutphen, ; Panguluri et al, ; Shen et al, ; Sutphen & Ferlita, ; Whitfield‐Broome, Dunston, & Brody, ), and three of Afro‐Caribbean populations (Akbari et al, ; Donenberg et al, ; Donenberg et al, ) and one study reporting SRAA of unspecified geography (Hall et al, ). From these papers, we identified 414 BRCA1 and 187 BRCA2 PSVs, and 108 unique BRCA1 and 103 unique BRCA2 PSVs.…”
Section: Resultsmentioning
confidence: 99%
“…Gao, Sveen, Cummings, & Olopde, 1998;Q. Gao et al, 2000;Gayol et al, 1999;Haffty et al, 2009;Hall et al, 2009;John et al, 2007;Kanaan et al, 2003;Kedar-Barnes et al, 2000;Lynce et al, 2015;Martin et al, 2009;Miki et al, 1994;Nanda et al, 2005;Olopade et al, 2003;Pal et al, 2008;Pal et al, 2015;Pal, Permuth-Wey, Holtje, & Sutphen, 2004;Panguluri et al, 1999;Shen et al, 2000;Sutphen & Ferlita, 1999;Whitfield-Broome, Dunston, & Brody, 1999), and three of Afro-Caribbean populations (Akbari et al, 2014;Donenberg et al, 2011;Donenberg et al, 2016) and one study reporting SRAA of unspecified geography (Hall et al, 2009). From these papers, we identified 414 BRCA1 and 187 BRCA2 PSVs, and 108 unique BRCA1 and 103 unique BRCA2 PSVs.…”
Section: African Ancestry Individuals With Brca1/2 Pathogenic Sequementioning
confidence: 99%
“…The frequency of mutations is highest in women diagnosed with breast cancer at an early age, women with a strong family history of breast or ovarian cancer, among women with triple negative breast cancer as well as women from ethnic heritages associated with founder mutations (e.g., Ashkenazim) [18,19]. Although some initial studies suggested that mutation prevalence might be lower among women from African than European ancestry, recent evidence demonstrates that prevalence is similar or possibly even higher among AA women in the USA [20][21][22][23][24][25][26][27][28]. Lynce and colleagues, for example, identified BRCA1/2 mutations in one of every seven self-identified AA from an unselected urban clinic population who met criteria for testing [28].…”
Section: Identification Of Carriersmentioning
confidence: 99%
“…Although some initial studies suggested that mutation prevalence might be lower among women from African than European ancestry, recent evidence demonstrates that prevalence is similar or possibly even higher among AA women in the USA [20][21][22][23][24][25][26][27][28]. Lynce and colleagues, for example, identified BRCA1/2 mutations in one of every seven self-identified AA from an unselected urban clinic population who met criteria for testing [28]. Similarly, Pal and colleagues found that 12.4 % of AA breast cancer patients under age 50 carried mutations in BRCA1/2 [27].…”
Section: Identification Of Carriersmentioning
confidence: 99%